MIT characteristic of VO2 thin film deposited by ALD using vanadium oxytriisopropoxide precursor and H2O reactant - Shin, Changhee; Lee, Namgue; Choi, Hyeongsu; Park, Hyunwoo; Jung, Chanwon; Song, Seokhwi; Yuk, Hyunwoo; Kim, Youngjoon; Kim, Jong Woo; Kim, Keunsik; Choi, Youngtae; Seo, Hyungtak; et al. (Journal of Ceramic Processing Research, 2019)
VO2 is an attractive candidate as a transition metal oxide switching material as a selection device for reduction of sneak-path current. We demonstrate deposition of nanoscale VO2 thin films via thermal atomic layer deposition (ALD) with H2O reactant. Using this method, we demonstrate VO2 thin films with high-quality characteristics, including crystallinity, reproducibility using X-ray diffraction, and X-ray photoelectron spectroscopy measurement. We also present a method that can increase uniformity and thin film quality by splitting the pulse cycle into two using scanning electron microscope measurement. We demonstrate an ON / OFF ratio of about 40, which is caused by metal insulator transition (MIT) of VO2 thin film. ALDdeposited VO2 films with high film uniformity can be applied to next-generation nonvolatile memory devices with high density due to their metal-insulator transition characteristic with high current density, fast switching speed, and high ON / OFF ratio.
Keywords: Atomic layer deposition; Metal insulator transition; Selection device; Sneak-path current; Vanadium dioxide